Analisis Perbandingan Rasio Profitabilitas Sebelum dan Sesudah Fatwa Boikot MUI Pada Perusahaan Food & Beverage Yang Terafiliasi Israel Di Bursa Efek Indonesia - Gustarina, Elina Rahmawati (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2024)
This study was conducted to compare profitability ratios using Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Operating Profit Margin (OPM) before and after the MUI Boycott fatwa on Food Beverage Companies affiliated with Israel on the Indonesia Stock Exchange (IDX). The data used were secondary data obtained from the Indonesia Stock Exchange (IDX) using the financial reports from Eleven FB companies in the third fourth quarters of 2023 and the first and second quarters of 2024. The analysis technique used were quantitative comparison. The results of this study indicate that the Profitability Ratio of massive Food Beverage Companies boycotted because they were affiliated with Israel on the Indonesia Stock Exchange has decreased from the period before and after the MUI Boycott Fatwa was issued